The Impact of Carbon Support Catalyst from Lignin-Derived Phenolic in Ozonation Process - Budi Satria Panandita; Lalak Tarbiyatun Nasyin Maleiva (Jurnal Inovasi Teknik Kimia, 2026)
The research described herein evaluated the effectiveness of a carbon-supported catalyst synthesized from lignin-derived phenol for ozonation, using methylene blue (MB) as a representative wastewater pollutant. The effectiveness of the degradation process was evaluated through kinetics. Furthermore, the effect of temperature on MB oxidation was investigated. The N2-sorption analysis confirmed a specific surface area of the carbon support of 36.16 m²/g, with a corresponding average pore radius of 1.58 nm. Fe-loaded carbon support achieves MB decolorization over 90% within 30 minutes. Pseudo-first-order and non-linear kinetic models described the catalyst's performance. The decolorization process was thermodynamically demonstrated to be endothermic and non-spontaneous.